Is the exosome a potential target for cancer immunotherapy? - Yoshimura, Akihiko; Sawada, Kenjiro; Kimura, Tadashi (Annals of Translational Medicine; Vol 5, No 5 (March 15, 2017): Annals of Translational Medicine, 2017)
Exosomes are nano-sized (30–100 nm in diameter) membrane vesicles of endocytic origin, which interact with other cells by transferring proteins, lipids, DNA, mRNA, and microRNA (miRNA) (1,2). Exosomes have diverse biological functions depending on the cell type of origin, such as tumor cell invasion, intercellular communication, and antigen presentation (3,4). In 2012, Peinado et al. (5) revealed that highly metastatic melanomas could reprogram bone marrow progenitor cells through transferring the receptor tyrosine kinase MET via exosomes, and thus increase their metastatic ability. Subsequently, Hoshino et al. (6) demonstrated that tumor-derived exosomes uptaken by organ-specific cells prepare the pre-metastatic niche. Specifically, exosomal integrins α6β4 and α6β1 were associated with lung metastasis, while exosomal integrin αvβ5 was linked to liver metastasis. More recently, Nakamura et al. (7) reported that ovarian cancer-derived exosomes transfer CD44 to surrounding peritoneal mesothelial cells, thereby facilitating cancer invasion.